2014
DOI: 10.1186/1471-2466-14-114
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics modifications and Subclinical Atherosclerosis in Obstructive Sleep Apnea: The EPIOSA study

Abstract: BackgroundObstructive sleep apnea (OSA) is associated with increased risk for cardiovascular morbidity and mortality. Epidemiological and animal models studies generate hypotheses for innovative strategies in OSA management by interfering intermediates mechanisms associated with cardiovascular complications. We have thus initiated the Epigenetics modification in Obstructive Sleep Apnea (EPIOSA) study (ClinicalTrials.gov identifier: NCT02131610).Methods/designEPIOSA is a prospective cohort study aiming to recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…There is at least one ongoing 5‐year study evaluating DNA methylation and RNA transcriptome changes in the blood of OSA patients (Marin et al . ); results of this study will be of considerable interest.…”
Section: Introductionmentioning
confidence: 87%
“…There is at least one ongoing 5‐year study evaluating DNA methylation and RNA transcriptome changes in the blood of OSA patients (Marin et al . ); results of this study will be of considerable interest.…”
Section: Introductionmentioning
confidence: 87%
“…Additionally, only one study with adults has aimed to evaluate the epigenetic mechanism involved in SAHS, but it has only published methodological data so far [54]. On the other hand, studies of DNA methylation patterns carried out in children with SAHS suggested an epigenetic dysregulation of vascular function [55].…”
Section: Discussionmentioning
confidence: 99%
“…Demographic, anthropometric, and clinical data were obtained at recruitment using specific questionnaires and standard measurements [12]. Daytime somnolence was assessed with the Epworth test [28].…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…The Epigenetics Status and Subclinical Atherosclerosis in Obstructive Sleep Apnea (EPIOSA) Study is a longitudinal study with the main objective of identifying epigenetic markers associated to the prevalence and progression of subclinical atherosclerosis in individuals with OSA without co-morbid conditions (ClinicalTrials.gov: NCT02131610) [12]. We hypothesized that adults with OSA may have different systemic inflflammatory responses reflflecting different patterns in FOXP3 gene methylation and expression.…”
Section: Introductionmentioning
confidence: 99%